Effect of gut microbiota early in life on aggressive behavior in mice. (July 2021) - Watanabe, Natsuru; Mikami, Katsunaka; Hata, Tomokazu; Kimoto, Keitaro; Nishino, Ryo; Akama, Fumiaki; Yamamoto, Kenji; Sudo, Nobuyuki; Koga, Yasuhiro; Matsumoto, Hideo
Highlights: Germ-free mice show more aggressive behavior than ex-germ-free mice. Germ-free mice inoculated with ex-germ-free mice feces reduced aggression. Brain dopamine levels were higher in germ-free than those in ex-germ-free mice. The gut microbiota early in life has an effect on aggressive behavioral traits. The gut microbiota can affect brain development and behaviors of the host. Abstract: Recent reports have indicated that gut microbiota modulates the responses to stress through the microbiota-gut-brain axis in mice, suggesting a connection between gut microbiota and brain function. We hypothesized that the gut microbiota early in life would have an effect on aggressiveness, and examined how gut microbiota affect aggressive behaviors in mice. BALB/c mice were housed in germ-free (GF) and ex-germ-free (Ex-GF) isolators. An aggression test was performed between castrated and a non-castrated mice at 8 weeks of age; the mice were allowed to confront each other for 10 min in strictly contamination-free environments. To evaluate aggressive behavior related to gut microbiota, we orally administered diluted Ex-GF mouse feces to the offspring of GF mice at 0, 6, and 10 weeks. GF mice showed more aggression than Ex-GF mice. Furthermore, GF mice who were administered feces of the Ex-GF group at 0-week-old were less aggressive than the GF mice. These findings suggested that the gut microbiota in the early stages of development was likely to have an effect on aggressiveness. Maintenance of healthy gut microbiota early in life can affect the mitigation of aggressive behavioral characteristics throughout the lifetime.